Cyclic ADP ribose as a calcium-mobilizing messenger. - Galione, A; Churchill, G (2000)
This Perspective by Galione and Churchill is one in a series on intracellular calcium release mechanisms. The authors review the evidence for cyclic adenosine diphosphate ribose (cADPR) being a second messenger involved in regulating intracellular calcium. In addition, the physiological stimuli and responses mediated by cADPR are discussed. The Perspective is accompanied by a movie showing a calcium wave triggered by cADPR.